Playing in Politics Towards the Better Education Policy in Indonesia - Juniar Laraswanda Umagapi (Magister Ilmu Politik Universitas Hasanuddin, 2016)
Emily Durkheim concluded that education could be reform only if society itself is reformed. He argued that education is the only image and reflection of society. Right now people just focus on the theory rather than practice in the education system. Even education right now cannot separated with the politics. Politics play an important rule towards the better education system. The issue about the new minister of education and the withdrawal of the previous minister influence their policy also in the curriculum system. Indonesia has the fourth largest education system in the world yet in a landmark education report of 50 nations Indonesia ranked last.The future success of communities and thus nations depends on today’s youth and the education they access. Nowhere is education more important than in the world’s poorest communities. A lot of stigma that playing politics can give and advantage of maybe disadvantage for the education system in Indonesia.